Serum sarcosine increases the accuracy of prostate cancer detection in patients with total serum PSA less than 4.0 ng/ml - Lucarelli, Giuseppe; Fanelli, Margherita; Larocca, Angela Maria Vittoria; Germinario, Cinzia Annatea; Rutigliano, Monica; Vavallo, Antonio; Selvaggi, Francesco Paolo; Bettocchi, Carlo; Battaglia, Michele; Ditonno, Pasquale (The Prostate, 2012)
BACKGROUND Sarcosine is reported to be a differential metabolite that is greatly increased during prostate cancer (PCa) progression. In this study, we assessed the role of serum sarcosine as a biomarker for PCa, as well as any association between sarcosine levels and clinical–pathological parameters. METHODS Sarcosine was measured by fluorometric assay in serum samples from 290 PCa patients and 312 patients with no evidence of malignancy (NEM), confirmed by 8–12 core prostate biopsies. Nonparametric statistical tests and receiver operating characteristics (ROC) analyses were performed to assess the diagnostic performance of sarcosine in different (prostate‐specific antigen) PSA ranges. RESULTS ROC analyses in subjects with PSA < 4 ng/ml showed a higher predictive value of sarcosine (AUC = 0.668) versus total PSA (AUC = 0.535) (P = 0.03), whereas for the other two PSA ranges (4–10 ng/ml and >10 ng/ml), percent ratio of free to total PSA (%fPSA) showed a predictive superiority over sarcosine. Moreover, in patients with a PSA < 4 ng/ml, the percentage of low/intermediate‐grade cancers was positively associated with sarcosine levels (P = 0.005). The specificities for serum sarcosine, %fPSA, PSA, and the logistic regression model at 95% sensitivity were 24.4, 3.41, 2.22, and 28.4%, respectively. CONCLUSIONS We provide evidence that serum sarcosine has a higher predictive value than tPSA and %fPSA in patients with PSA < 4 ng/ml. Moreover, sarcosine levels were significantly different in low grade versus high grade cancers in this subset of patients, suggesting that this marker may be a further tool not only for diagnosing PCa in normal PSA and abnormal DRE/TRUS patients but also for selecting candidates for non‐aggressive therapies and active surveillance. Prostate 72:1611–1621, 2012. © 2012 Wiley Periodicals, Inc.